Several Examples of Two-piece Serpentine Fibulae from Dalmatia (Archaeologia Adriatica, 2017)
This paper deals with four recently published two-piece serpentine fibulae from Dalmatia, from the central Liburnian area. More recent classification of fibulae was considered as well as their function in the female attire. Fibula from Jokina Glavica was compared with fibulae from Italy regarding certain details.
Keywords: two-piece serpentine fibula; Jokina Glavica; Dragišić; Šopot-Perušić